Corporate Social Responsibility and Firm Value with Profifitability, Firm Size, Managerial Ownership, and Board of Commissioners as Moderating Variables - Eko Sugiyanto; Rina Trisnawati; Eny Kusumawati (Riset Akuntansi dan Keuangan Indonesia, 2021)
The purpose of this study was to analyze the influence of CSR on firm value with profitability, company size, managerial ownership and board of commissioners as moderating variables. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. The sample was determined by purposive sampling technique and obtained a sample of 154 companies . This research uses statistical analysis by regression analysis with moderating variables. The results in this study are corporate social responsibility had  affect the value of the company. Company profitability and size can moderate the relationship of CSR to firm value. Whereas managerial ownership and the board of commissioners cannot moderate the relationship of CSR to the value of the company).